Wellness in South Africa - Roy Jobson (South African Family Practice)
Wellness is a term increasingly being used in South Africa society. However it's use is inconsistent and confusing. Even certain medical aids are using the term to promote their particular products ans increase their membership claiming to be offering their clients something 'special' and 'different'. Many complementary and alternative medicine practitioners have also jumped onto the Wellness bandwagon. 'Stress management' features prominently. Some biokineticits and exercise physiologists use Wellness to describe their particular approaches.